Iowa Birdline update, October 22, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al
Email of the Iowa Birdline update for October 22, 1990. Highlights of the update include the continued presence of a California Gull, a Mute Swan, and a Scissor-tailed Flycatcher. Also of note was the large numbers of waterfowl spreading across the state. Other interesting observations were of Carolina Wrens, a Short-eared Owl, and numerous Sparrow species, including a Harris' and a Le Conte's Epson - sheet feed/flatbed